Pengaruh Kompensasi dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT. Semen Indonesia Unit Tonasa Kabupaten Pangkep - Romansyah Sahabuddin; Zainal Ruma; Burhanuddin Burhanuddin; Uhud Darmawan Natsir; Astuti Astuti (Jurnal Mirai Management, 2023)
The purpose of this research is to know and explain the effect of job satisfaction and compensation on employee performance. The type of research used is quantitative research with two independent variables consisting of job satisfaction (X1) and compensation (X2) and the dependent variable of employee performance (Y). the subject of this research is an associate position employee at PT. Semen Indonesia Tonasa unit, Pangkep district, the sampling technique in this study used the slovin formula, totaling 115 respondents. Data collection used questionnaires or questionnaires while data analysis techniques used data using multiple linear regression analysis with hypothesis testing using the t test and f test. The results of the study show that job satisfaction has a significant effect on employee performance as indicated by the partial test that the results of the t test for the satisfaction variable obtained t count of 21.334 while t table is 1.661 and has a significant number of 0.000